Syndrome Coronary Acute: an approach to its impact on cardiology (Research, Society and Development, 2022)
Acute Coronary Syndrome (ACS) is an ischemic process of the myocardium arising from cardiac hypoperfusion, resulting from the rupture of atherosclerosis or by a clot in the coronary arteries. There are several indications for the suspicion of ACS, such as the typical chest pain and shortness of breath, where the group of elderly, diabetics and women already makes it possible to consider the diagnosis. The following article aimed to describe in a narrative way the most relevant aspects regarding acute coronary syndrome. To carry out this research, the following health descriptors were used: directed to the renowned platforms that made full articles available in Portuguese, English and Spanish. Based on the information collected in the literature, it can be clarified that ACS is a medical emergency, whose clinical outcome is determined by early diagnosis and treatment. Thus, it is essential to obtain as much information as possible in the clinical history, associate the findings of the physical examination and complementary means for the adequate management of ACS, symptomatic relief and prevention of morbidity and mortality.